BASIC SOCIAL STEREOTYPES IN TEACHING MARKETING - Lyubov' M. Naumova (Moscow Polytechnic University, 2016)
In the last decade the number of students enrolled on the first course of Russian universities, almost equal to the number of high school graduates. As a result the higher school teachers have to teach poorly motivated students with low levels of schooling. To increase the effectiveness of the training of these students the author encourages to use marketing technologies and simulate the process of learning as promotion (or even imposition) non(popular products (knowledge and skills) to weakly motivated buyers (the student). As a marketing tool we use some elements of influence technology developed by the American social psychologist Robert Cialdini. At the heart of these technologies are the basic socio( psychological stereotypes of personality. The action of such stereotypes as goodwill, mutual exchange, social proof and others was considered. The use of marketing tools in educationimproves leaning efficiency and reduces the psychological burden of a teacher, preventing the probability of professional burnout.